The Impact and Benefits of the Digital Health Technology Management System Model on Environmental Public Health Underserved Thai People and Stakeholders - Wongsrikaeo, Jumnean; Tulachom, Prachayakul; Wongpho, Bunlert; Santiboon , Toansakul T. (Journal of Ecohumanism, 2024)
Thailand has been invested in digital health to improve health outcomes and well-being. The Ministry of Public Health has published a Digital Health Strategy (2021-2025), there are the key roles digital technologies can play in strengthening the health system. The Thai population should know the concepts of the digital health management system model (DHMSM) on environmental public health (EPH) with mHealth and eHealth data in the future in medical devices and allied technologies toward digital health. Designing mixed research methodology was administered with the original raw data from Documentary Research reviewed data management in the digital health management system model, digital health environment, and public attitudes toward digital health management system models for the environmental health of strategic direction for digital health risks are impacted and beneficial to 400 Thai patients, people, and stakeholders at the 4-Local Health Centers under the strategies and policies of the Ministry of Public Health of Thailand were assessed of their perceptions on the 36-item Benefits of the Digital Health Management System Model on Environmental Public Health (BDHTs) on six scales and the 35-item Questionnaire on the Impact of the Digital Health Management System Model on Environmental Public Health (IDHTs) on seven scales; each scale of two research instruments are independent variables, and the 24-item Public Attitudes Toward Digital Health Management System Models for Environmental Health (PADHTs) with the grand mean scores are dependent variable. In correlational research, relationships between the variables are associated with simple and multiple correlations and the regression coefficient is correlated and significant. The R2 coefficient values indicate that 71% and 79% of the variance in participants’ guidelines of their attitudes on the benefits and impact of the DHMS on Environmental Public Health risks to promote wellness that its’ impact and benefits to Thai patients are provided.